The Beneficiary's case in Quechua and Spanish - Calvo, Julio (2023)
This article discusses the role of the pragmatic internal suffix -pu- of Quechua, correlated with -mu-, and its complex relationship with the casual peripheral suffix -paq, in order to warn about its syntactic-pragmatic dysfunctionality despite covering semantically both the Recipient field. It will also be analyzed if there is a similar parallelism between the unstressed pronouns (me, te, se, lo...), the suffix -ario and the preposition para in the Spanish language. The Quechua-Spanish contrast will make it possible to ensure that the pragmatic projection is similar in the two languages, although morphologically and syntactically they are so different.